CLASP promotes stable tethering of endoplasmic microtubules to the cell cortex to maintain cytoplasmic stability in Arabidopsis meristematic cells. - P Yen Le; Chris Ambrose (PLoS ONE, 2018)
Following cytokinesis in plants, Endoplasmic MTs (EMTs) assemble on the nuclear surface, forming a radial network that extends out to the cell cortex, where they attach and incorporate into the cortical microtubule (CMT) array. We found that in these post-cytokinetic cells, the MT-associated protein CLASP is enriched at sites of EMT-cortex attachment, and is required for stable EMT tethering and growth into the cell cortex. Loss of EMT-cortex anchoring in clasp-1 mutants results in destabilized EMT arrays, and is accompanied by enhanced mobility of the cytoplasm, premature vacuolation, and precocious entry into cell elongation phase. Thus, EMTs appear to maintain cells in a meristematic state by providing a structural scaffold that stabilizes the cytoplasm to counteract actomyosin-based cytoplasmic streaming forces, thereby preventing premature establishment of a central vacuole and rapid cell elongation.